Beneficiation from coal washing tailings and biomass in active carbon and humate mud production - Tosun, Yıldırım İsmail (Fırat Universitesi, 2017)
Pyrolysis and processing biomass with coal may provide active carbon souce. Tailings of coal washing plants contained coal source for active carbon production and agricultural biomass wastes could be mixed together with this tailings providing sufficient active carbon char quality for organic fertility of soil remediation. 27% relatively more fertile humate production could be managed by active carbon mix of coal washing tailings to soil.
Keywords: Coal Washing Tailings; Biomass; Active Carbon; Humate mud